Carotid plaque hemorrhage on magnetic resonance imaging strongly predicts recurrent ischemia and stroke - Hosseini, Akram A.; Kandiyi, Neghal; MacSweeney, Shane T. S.; Altaf, Nishath; Auer, Dorothee P. (Wiley, 2013)
Objective There is a recognized need to improve selection of patients with carotid artery stenosis for carotid endarterectomy (CEA). We assessed the value of magnetic resonance imaging (MRI)-defined carotid plaque hemorrhage (MRIPH) to predict recurrent ipsilateral cerebral ischemic events, and stroke in symptomatic carotid stenosis.